Applying the TAM and TOE Integrated Framework in Researching the Social Media Adoption in Retail Businesses in Vietnam - Thi Huong, Dang; Ngoc, Luu Thi Minh; Mai, Nguyen Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 1, 2020)
Social media has been growing and strongly impacting on retail businesses in Vietnam. With the advantages of applying social media in business, online retail businesses have become popular and effective. Based on the synthesis of the theory of social media and the models related to technology adoption behaviours of enterprises (TAM model and TOE model), the article proposes a research framework on factors affecting the decision to adopt social media in retail business in Vietnam.